Expression of Twist increases the risk for recurrence and for poor survival in epithelial ovarian carcinoma patients - Satoyo Hosono; Hiroaki Kajiyama; Mikio Terauchi; Kiyosumi Shibata; Kazuhiko Ino; A. Nawa; Fumitaka Kikkawa (2007)
Twist is a transcription factor that regulates the expression of tumour suppressors such as E-cadherin. We examined the distribution and expression of Twist in human epithelial ovarian carcinoma (EOC) to examine its clinical significance. Paraffin sections from EOC tissues (n=82) were immunostained with Twist antibody, and the staining intensity was evaluated. The clinicopathological factors examined were age, International Federation of Gynecology and Obstetrics staging, histological type, tumour grade, preoperative value of CA125, peritoneal cytology, volume of ascites and residual tumour after cytoreductive surgery. Overall survival (OS) and progression-free survival (PFS) were evaluated using the Kaplan-Meier method, and multivariate analysis was performed using the Cox proportional hazard analysis. Of the 82 carcinomas, 49 (59.8%) cases were negative for Twist immunoexpression, and 33 (40.2%) were positive immunoexpression. When categorized into negative vs positive expression, Twist was not associated with any of the clinicopathological parameters examined. However, positive Twist expression significantly predicted poorer OS and PFS when compared with negative expression (P<0.0001). In the multivariate analyses, positive Twist expression was the only independent prognostic factor for survival in this study (P<0.0001). Positive Twist expression seems to be a useful marker in patients with EOC likely to have an unfavourable clinical outcome.